The geology of the Matala Dome: an important piece of the Pan-African puzzle in Central Zambia - Naydenov, K. V.; Lehmann, J.; Saalmann, K.; Milani, L.; Poterai, J.; Kinnaird, J. A.; Charlesworth, G.; Kramers, J. D. (International journal of earth sciences : Geologische Rundschau, 2016)
The Matala Dome (MD), an ENE-trending structure located at the junction between the Pan-African Lufilian and Zambezi belts, is cored by a Gneiss-Schist Unit with uncertain age overlain by a metasedimentary section (Quartzite-Schist Unit, Marble Unit and Carbonate-Siliciclastic Unit) of the Neoproterozoic to Cambrian Katanga Supergroup. The top of the Katangan stratigraphy is represented by synorogenic sedimentary rocks—Upper Siliciclastic Unit. An early event D1 resulted in the development of shallow-dipping metamorphic foliation S1 and pre- to syntectonic growth of garnet and kyanite in the schists of the Quartzite-Schist Unit. Pseudosections and garnet isopleth modelling on schist from this unit defined the peak metamorphism at P = 7.5–9.3 kbar and T = 620–700 °C. U–Pb detrital zircon dating revealed ca. 2.7 Ga source and a high-grade metamorphism during Pan-African times. The S1 foliation was affected by upright folding F2 with ENE-trending axes and associated subvertical crenulation fabric S2 development. The syn-D2 retrogression in the schists is marked by post-S1 staurolite crystallisation and further by chloritisation followed by sericitisation. The D2 event is interpreted to have exhumed the orogenic middle crust and to be responsible for the domal structure of the MD. 40 Ar/ 39 Ar dating of muscovite at 529.3 ± 5.6 to 526.3 ± 6.2 is interpreted to date the exhumation event. D2 is correlated with regional N–S shortening event at ca. 530–520 Ma. Based on the lithology, structural record, and time and facies of the metamorphism, a correlation between the MD and the northern part of the Zambezi Belt is suggested.